The Role of School Management Committee and Pupils' Performance in Government Primary Schools in RuhiJa Town Council Rubanda District. (Kabale University, 2023)
Participation of School Management Committee members in meetings was one of the ways through which pieces of advice would be provided to the school stakeholders including teachers, learners, head teachers, casual labourers all aimed at shooting in a direction of uplifting the pupils' academic performance (Lamb, 2007). The study was conducted aimed to investigating the role of school management committee on pupils' performance in primary schools in Ruhija Town Council Rubanda District. It adopted cross-sectional survey design alongside qualitative and qualitative paradigms. Questionnaires and interview guides were used to collect data for the study. Sample Size considered only 222 respondents. The objectives included; establishing the impact of advisory role towards pupils' performance; examining the effect of supervisory role on pupils' performance and finally, ascertaining the contribution of empowerment role on pupils' performance in primary schools. The major findings included; advising through meetings which had 60(27%) ofrespondents, supervision involving cooperation towards pupils' performance that bad 3.49 mean score and the standard deviation of 0.839; and School Management Committee to participate in leading to reduced number of children in school that had 35% of the respondents. The study concluded mentioning the role of school management committee on pupils' performance in primary schools in Ruhija Town Council Rubanda District not to have been worth due to a number of loopholes detected in members of the school management committee of certain schools which included but not limited to; development of a culture of not trusting the employees that they could improve academic standards, school management committees disrespecting teachers leading to reduced enrollment of the school and failure of school management committees to understand the responsibilities of each employee in school. Thus, there was need for more research about the role played by the cohort mentioned as to improve on pupils' academic performance. The recommendations included; the school management committee through meetings with members of teaching staff and their head teachers should advise them properly and allow them to execute their duties as expected in order to alleviate levels of understanding to children that lead to excellent academic performance; more research should be carried out to allow the school management committees not to dwell on advising head teachers only on matters of children's performance by suggesting strategies but also the entire stakeholders whose effort can promote academic performance of children in primary schools; need to formulate academic committees advised by the members of school management committee on how to perform through motivational element aiming at doing well academically to promote the names of the school; it is imperative that the schools get in touch with the members of the school management committees who have some formal education to quickly understand the value of education and how plans for developments of certain sectors in school especially academic performance could be made; need to foster supervision that involves cooperation towards pupils 'performance by all stakeholders; appointing an active team that can do supervision to let children advance academically is healthy.